"Der Wechsel - Erleichterung des Geldverkehrs": Der Versuch der Einführung einer Wechselordnung in den Herzogtümern Schleswig und Holstein 1842 - Peter Wulf (IBF - Institut für Bank- und Finanzgeschichte, 2019)
– The bill of exchange has a long history as a general instrument for monetary transactions. The main financial centers made wide use of this tool. The prerequisites were a functioning banking system as an intermediary, as well as a legal framework for bill of exchange transactions. Although neither of these existed in Schleswig-Holstein until the mid-19th century, economic development in Germany at the time called for the introduction of such a legal set up. This paper highlights the obstacles that had to be overcome in this respect in what is a predominantly agricultural region.
Keywords: N23; 330